2009
DOI: 10.1161/circulationaha.108.822072
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Phosphodiesterase-5 Expression Is Increased in Patients With Advanced Heart Failure and Contributes to Adverse Ventricular Remodeling After Myocardial Infarction in Mice

Abstract: Background Ventricular expression of phosphodiesterase-5 (PDE5), an enzyme responsible for cGMP catabolism, is increased in human right ventricular hypertrophy, but its role in left ventricular (LV) failure remains incompletely understood. We therefore measured LV PDE5 expression in patients with advanced systolic heart failure and characterized LV remodeling after myocardial infarction (MI) in transgenic mice with cardiomyocyte-specific over-expression of PDE5 (PDE5-TG). Methods and Results Immunoblot and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
146
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 33 publications
13
146
2
2
Order By: Relevance
“…The cGMP‐PKG‐PDE5 signaling axis has been hypothesized to contribute to the pathophysiology of human HF 6, 50, 51, 52. However, this finding is not definitive in a setting of human HFpEF5, 9 where clinical data have failed to show benefits previously reported in multiple animal models 47, 50.…”
Section: Discussionmentioning
confidence: 96%
“…The cGMP‐PKG‐PDE5 signaling axis has been hypothesized to contribute to the pathophysiology of human HF 6, 50, 51, 52. However, this finding is not definitive in a setting of human HFpEF5, 9 where clinical data have failed to show benefits previously reported in multiple animal models 47, 50.…”
Section: Discussionmentioning
confidence: 96%
“…It was recently reported that PDE-5 is up-regulated in patients with end-stage heart failure; however, 2 μM SIL was used for cGMP PDE assays as a test for PDE-5 activity (54). At this concentration, SIL can inhibit most of the cardiac PDE-1C activity (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The rise in right ventricular contractility was due to an intrinsic myocardial effect because the pulmonary arteries were no longer present and could therefore not contribute to reduced right ventricular afterload. Pokreisz et al 47 confirmed that PDE-5 expression is greater in left ventricular myocardium of patients with HF compared to controls. To determine the impact of elevated PDE-5 levels in diseased left ventricles, the authors compared the effect of a myocardial infarction on mice with increased PDE-5 expression versus wild type.…”
Section: Mechanisms Of Pde-5 Inhibitors Improving Hfmentioning
confidence: 92%